(untitled) (Fiep Bulletin - online, 2015)
The aging of the population already encloses the developing countries. Investment in studies that promote better quality of life for these individuals is important. The fall is one of the problems that affect negatively the quality of life of old people. Loss of the balance is considered to be one of the important causes of the falls among the elderly. Many studies have been carried through to identify which falls prevention strategies are efficient to improve balance. Tai Chi Chuan exercises bring good results in relation to the improvement of balance and reduction of the risks of falls. We made a bibliographical review to verify the relation between the exercises of Tai Chi and the improvement of the balance, the proprioception and reduction of the risks of falls in the elderly. According to the research Tai Chi practitioners show good results in balance and proprioception tests and in the reduction of the number of falls. Tai Chi shows significant benefits in relation to the postural control. The literature is still inconsistent in relation to the assessment of the factors that are responsible for the improvement of the balance and also in relation to the how the proprioception is improved. Further studies are required to obtain a more precise assessment of the effectiveness of the exercises of Tai Chi Chuan